Egg white-induced inflammation models: A study of edema profile and histological change of rat's paw - Elisabeth Natalia Barung; Jovie Mien Dumanauw; Meilany Feronika Duri; Donald Emilio Kalonio (Wolters Kluwer Medknow Publications, 2021)
The egg white was used to induce rat paw inflammation, with inadequate references to explain its mechanism. It's contained protein was identified as an allergen was suspected to trigger an inflammatory reaction. This research was aimed to evaluate the use of egg white as an inflammatory inductor in inflammation animal models through edema profile and histological change. Male Wistar rats were divided into three groups, which were given λ-carrageenan, fresh takes of the hen's egg white, and sterile saline solution. Edema was induced by subcutaneous injection of 0.1 ml of λ-carrageenan (1%), egg white, and sterile saline solution as the control in the hind paw of rats. Paw volume was measured before and then at 1, 2, 3, 4, 5, 6, and 24 h after the inductor injection. Paw tissue was taken for evaluation of rats' paw histological change. The data were analyzed by one-way ANOVA followed by LSD test. The results of the study showed that the egg white could induce rat paw inflammation. Edema formation began in the 1st h and reached the peaks in the 2nd h after the subcutaneous injection of egg white. A number of leukocyte cells were also found in the inflamed paw tissues. Egg white was potential as an edema inductor for animal models of inflammation for the evaluation of new drugs or natural product with anti-inflammation activity.